Peningkatan Kualitas Pelayanan Publik Melalui Desain Renovasi dan Ekstensi Infrastruktur Kantor Kelurahan Selat Barat Kabupaten Kapuas - Ahmad Rafli Hambali; Amanda Febri Putri Utama; Yoel Landa; Dea Ekklesia Anastasia Saragih; Zefanya Elva Theadora; Felix Owen; Idwanto Permana; Purmasari Purmasari (Fakultas Teknik Universitas Palangka Raya, 2026)
Community Service Program (KKN) is a form of learning activity that provides students with the opportunity to interact directly with the community and apply the knowledge they have acquired in lectures. The TMB KKN program aims to provide field learning experiences, develop creativity, innovation, independence, interdisciplinary collaboration skills, and the application of students' hard and soft skills in the context of community development. The implementation of KKN TMB Group 9 was carried out in Selat Barat Village, Kapuas Regency, with a focus on extending the terrace into a waiting room for the village office to improve public services. The methods used were participatory and applicable, actively involving students in all stages, from preparation, field surveys, needs analysis, design, to reporting and evaluation. The data collected included the physical condition of the building, space and facility requirements, inventory of infrastructure, budget and funding sources, technical building standards, and unit prices for local labor and materials. The activities were supported by hardware such as laptops, external storage devices, smartphones, and printers, as well as software such as AutoCAD, SketchUp, Microsoft Office/Google Workspace, and team communication applications. The results of the activity show that students successfully designed the layout and prepared a Budget Plan (RAB) for the village office, as well as strengthening collaboration between students, village officials, and the community. This program makes a real contribution to improving the quality of public services as well as providing science and technology-based learning experiences for students.